Social differentiation, representation, government: Notes for a reflection on constitutional reforms (Sociologia del diritto, 2024)
From the end of the 1970s onwards, the idea that the excess of differentiation within complex societies puts pressure on the system of representation, making contemporary democracies ungovernable, has consolidated. The paper investigates the relationship between social differentiation, pluralism and representation from the crisis of the organicism of the Ancien Régime up to the debate on constitutional reforms in Italy, focusing on the approach that the Constitution gives to the topic, in the belief that, if a problem friction exists, it is resolved by improving the representative capabilities of the system rather than by increasing the powers of the Government.
Keywords: Social differentiation; Pluralism; Representation; Government; Reforms; Premiership